Brain-derived Neurotrophic Factor and TrkB Levels in Mice that Lack Vesicular Zinc: Effects of Age and Sex. (15th January 2020) - McAllister, Brendan B.; Bihelek, Nicoline; Mychasiuk, Richelle; Dyck, Richard H.
Highlights: BDNF and TrkB levels were measured in the hippocampus and neocortex of ZnT3 KO mice, which lack vesicular zinc. BDNF and TrkB protein levels in young (5 week) and mature (12 week) wild type and ZnT3 KO mice of both sexes were compared. ZnT3 KO mice exhibited normal BDNF protein levels, though BDNF mRNA expression was increased in female ZnT3 KO mice. BDNF protein levels in both the hippocampus and neocortex increased with age in female, but not male, mice. TrkB protein levels were normal in ZnT3 KO mice, and male mice had greater neocortical TrkB protein levels than did females. Abstract: In certain neurons, zinc ions are stored in synaptic vesicles by zinc transporter 3 (ZnT3). Vesicular zinc can then be released synaptically to modulate myriad targets. In vitro evidence indicates that these targets may include brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin receptor kinase B (TrkB). But the effects of vesicular zinc on BDNF and TrkB in the intact brain are unclear. Studies of mice that lack ZnT3 – and, as a result, vesicular zinc – have shown abnormalities in BDNF and TrkB levels, but results have been mixed and are therefore difficult to interpret. This might be caused by differences in the age or sex of mice tested. In the present study, we measured BDNF and TrkB levels in the hippocampus and neocortex, comparing wild type and ZnT3 knockout mice of both sexes at two ages (5 and 12 weeks). We also examined BDNF mRNA expression and protein levels at an intermediate age (8–10 weeks). We found that, regardless of age or sex, BDNF and TrkB protein levels did not differ between wild type and ZnT3 knockout mice. There were sex-specific differences in BDNF protein and mRNA expression, however. BDNF protein levels increased with age in female mice but not in males. And in females, but not males, ZnT3 KO mice exhibited great hippocampal BDNF mRNA expression than wild type mice. We conclude that, at least in naïve mice housed under standard laboratory conditions, elimination of vesicular zinc does not affect BDNF or TrkB protein levels.